Nucleomethylin deficiency impairs embryonic erythropoiesis. (13th December 2017) - Murakami, Shohei; Suzuki, Takuma; Yokoyama, Wataru; Yagi, Satoko; Matsumura, Keita; Nakajima, Yuka; Harigae, Hideo; Fukamizu, Akiyoshi; Motohashi, Hozumi
Abstract: Nucleomethylin (NML) has been shown to contribute to ribosome formation through regulating transcription and post-transcriptional modification of rRNA. Based on the observation that NML –/– mice are frequently embryonic lethal, we analyzed NML –/– embryos to clarify the role of NML in embryogenesis. We found that NML deficiency leads to lethality at the time point between E10.5 and E12.5. Most of E10.5 NML –/– embryos exhibited growth retardation and/or malformation with marked impairment of erythropoiesis. Consistent with a previous study, the m 1 A in 28S rRNA was dramatically reduced in NML –/– foetal liver (FL) cells. Because the previous study demonstrated p53-dependent apoptosis of NML -knockdown cells, and because we observed upregulation of p21, one of the p53 target genes, in NML –/– FL cells, we tested whether p53 disruption cancelled the NML -deficient phenotypes. Contrary to our expectation, suppression of p53 did not rescue the lethality or impaired erythropoiesis of NML –/– embryos, suggesting that p53-independent mechanisms underlie the NML -deficient phenotypes. These results clarify an essential role of NML during embryogenesis, particularly in erythropoiesis. We surmise that embryonic erythropoiesis is particularly sensitive to impaired protein synthesis, which is caused by the defective methylation of rRNA and consequent failure of ribosome formation.